AIEgens with cyano-modification in different sites: Potential 'Meta-site effect' in mechanochromism behavior. (February 2022) - Wang, Mengshi; Wang, Yuanheng; Hu, Renjian; Li, Ruoxin; Shuai, Zhigang; Wei, Yen
Abstract: The current research of mechanochromic molecules focused on different molecular skeletons and the types of functional groups, where the design ideas were limited. We have synthesized a group of cyano-modified TPE derivatives (TPECN ) with different substitution sites, showing typical aggregation induced emission (AIE) effect. We found that meta-substituted mCN revealed the inertness of mechanochromism, whether being ball milled or rapidly evaporated. Isomers with ortho- or para-substitution showed an emission wavelength shift over 40 nm. Experimental data indicated unusual high-strength lattice stability for mCN . By single-crystal analysis and theoretical calculations, we clarified from the molecular skeleton distortion, noncovalent intermolecular interactions, and calculated interaction energy that the meta-substitution led to a stable lattice structure, making mCN insensitive to external stimuli. Thus, we successfully explained the substituted site was an important and independent factor that influenced the mechanochromic property. Meanwhile, we also explored the application of the TPECN s series for erasable printing and coding. Highlights: Differences in mechanochromism behavior between isomers were observed. Potential 'meta-site effect' in TPE-based AIEgen were shown. The relation between interaction energy of lattice and mechanochromism property was proposed. Powerful applications on the erasable printing and coding were achieved. Abstract : A potential 'meta-site effect' for mechanochromic AIEgens was observed through a group of cyano-modified TPE derivatives with the same functional group and the molecular formula but different substitution sites. The meta-substitution caused the slighter distortion for molecular conformation, the tighter stacking mode, the more numerous interactions, and the lower interaction energy out of three isomers, which enhanced the lattice stability and led to the inertness of mechanochromism.